Inequalities, barriers, intersectionality, and facilitators of careers of women with disabilities: Themes and future research agenda from a scoping review - Chan, Xi Wen; Hutchings, Kate (Frontiers in Psychology, 2023)
The increasing number of women in paid work over recent decades has resulted in substantive research on all aspects of women’s careers, yet examination of women in some minority groups has received much less attention. Extant research has found that although people with disabilities exhibit strong organisational loyalty and less absenteeism from work, they experience a disability pay gap, and are less likely to be working as managers or directors or in professional occupations. Experiences of prejudice, ableism, and discrimination lead to fear of disclosure, and this is accentuated in some economies and communities where there is stigma associated with having disabilities, especially mental illness. As women may experience a double disadvantage based on their gender and disability and have lower levels of employment than men with disabilities and women without disabilities, it is important to understand factors affecting the career motivations, opportunities, and development of this significant proportion of the (potential) workforce. This article presents a rapid review of the relevant literature and identifies key themes including career inequalities for women with disabilities, career barriers for women with disabilities, educational interventions to improve career motivations and opportunities for women with disabilities, facilitators for careers and career development of women with disabilities, and intersectionality of gender, disability, and other identities for women’s career development. Limitations of the review include the exclusion of grey literature and certain databases in the search process. Based on the analysis of the themes developed from the peer-reviewed literature examined, a future research agenda is established.